Enfermedad hidatídica diseminada con localización mediastinal como causa de síndrome de vena cava superior. - PINTO VALDIVIA, José Luis (2013)
Hydatidic illness is a frequent parasitic zoonosis in our country whose more frequent localization is the liver and the lungs. However other many sites have been described, depending their symptoms on the cyst’s size, localization and effect on next structures, being sometimes its evolution fatal. This is a 52 year-old female patient admitted at emergency room for dysfunction of sensory and neurological focalization. She had a previous history of surgery many years ago by abdominal tumor. We found a collateral circulation on right hemithorax and facial and arms edema at exam. The cerebral CT showed extensive left parietal parenchymal hemorrhage. Thoracoabdominal CT revealed multiple cystic masses of diverse sizes in the mediastinum, lungs, liver and other places. The patient’s evolution was torpid, the neurological compromise didn’t improve in spite of the treatment against the intracranial hypertension (EH), being also added a nosocomial pneumonia. The patient died after several days. Necropsy revealed presence of cystic lesions in mediastinum, heart’s great vessels, pericardium, lungs, liver, spleen and omentum, as well as intra and extraparenchymal hemorrhages of hypertensive cause in brain, not being cystic lesions in central nervous system. We concluded that it was disseminated hydatidic illness, cysts in the mediastinum caused compression of the heart’s great vessels, causing a superior cave vein syndrome. ( Rev Med Hered 2001; 12: 142-149 ).